Generalized Prefix Approach for Alamouti Coded OFDM Systems over Gaussian Channels Correlated in Space - Yıldız, Hakan; Cooklev, Todor; Doğan, Hakan; ACAR, YUSUF (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2014)
In this ivorkt, generalized frelix (GP) lbr space time block coded orthogonal frequency division multiplexing (STBC-OFDM) systems is considered in the presence of correlated channel. The 2x2 STBC case, in practice, lead to significant correlation among the spatial signatures and reduce the systems performance. There are several structures to reduce correlation. To solve this problem, we propose the generalized prefix that has low computational complexity. It is shown that the proposed generalized prefix thr 2x2 STBC-OFDNI outperforms the conventional 2:c2 STBC-OFDNI system.
Keywords: Generalized prefix; orthogonal frequency-division multiplexing (OFDM); space-time block code (STBC); channel correlation